The Archaeology of Water Management on the Swahili Coast of East Africa - Baumanova, Monika (The Archaeology of Irrigation Technology and Water Management in the Islamic World: Proceedings of the Bahrain Conference, January 2024, 2025)
The archaeology of irrigation technology and water management encompasses a wide range of structures – subterranean tunnels (qanāts, falaj, foggara, ghayl etc.), reservoirs, cisterns, canals, aqueducts, tanks, fountains, water mills, wells, dams, barrages - in a variety of contexts - mountains, deserts, forests, agricultural, horticultural, urban, village, military, riverine, estuarine, coastal, lacustrine – and over a long time period from the seventh through to nineteenth centuries. However, in many areas the archaeology of these facilities remains little explored. This volume begins to rectify this through a variety of case studies examining the diverse ways that past populations have developed hydraulic infrastructure for moving and managing water across the Islamic World. It also considers how past human ingenuity in developing hydraulic infrastructure, now often fallen into disrepair and dis-use, could hold lessons for the present and offer solutions for the future as humanity faces the challenges of environmental and climate change.
Keywords: Archéologie – Zanzibar

Ship graffiti at the Zanzibar Gereza (Old Fort), Stone Town, Unguja, Tanzania - Cooper, John P.; Ghidoni, Alessandro (Azania: Archaeological Research in Africa, 2022)
Keywords: Archéologie – Zanzibar